Peran Program BPNT dalam Meningkatkan Financial Well-Being dan Family Finance Keluarga Penerima di Kota Malang - Sandi Mustika Prayogo; Dharmayanti Pri Handini; Choirul Anam (Jurnal Manajemen Bisnis Era Digital, 2025)
The study stems from the significance of social aid as a tool for empowering low-income households. The Non-Cash Food Assistance (BPNT) program is designed not only to fullfill basic needs but also to support long-term improvements in family financial well-being. The study aims t explore how financial well-being and family finance are interpreted by both beneficiaries and government actors in Malang City. Employing a qualitative method with single-case study design,data were collected through in-depth interviews, direct observation, and document analysis. Finding reveal that financial well-being is perceived as a state of economic stability, demonstrated by the ability to meet essential needs, manage debt, and plan finances effectively. Meanwhile, family finance is expressed through disciplined budgeting, saving habits, and the implementation of financial literacy within the houshold. The study underscores that the success of social assistance program such as BPNT is largely dependent on beneficiaries’ financial management skills rathet than the nominal value of the aid.